Prevalence of Chlamydial antibody in populations from Brazil, England and Portugal - Ishak, Marluísa de Oliveira Guimarães; Mumtaz, Gilanfan; Ishak, Ricardo; Ridgway, Geoff (Revista do Instituto de Medicina Tropical de São Paulo, 1988)
The prevalence of group - specific antichlamydial IgG in populations from Brazil, England and Portugal was studied using the whole inclusion - indirect immunofluorescence test, and SA2 (f) as antigen. Those sera with the IgG titre > 1:32, were considered to be positive. Among the Brazilian populations, prevalence of chlamydial antibody was higher in Serra Norte (76,2%, p < 0,01) than in Belém (53,6%) and among Xicrins Indians (51,3%). In patients attending the Departament of Genito Urinary Medicine, University College Hospital and in members of the UCH staff, London, England, the prevalence of antichlamydial IgG was 62% and 53,1%, respectively. Antibody to Chlamydia was detected in 54% and 66% of the English women and in 56 and 68% of the Portuguese women attending Antenatal and Infertility Clinics, respectively. These results show a wide exposure to Chlamydia among all the populations tested, mainly among the low socio-economic group of Serra Norte, Brazil. Evidence of chlamydial infections is of the same order in Brazil, England and Portugal.